INDONESIA LOGISTICS SECTOR REVIEW: PERFORMANCE, CHALLENGES, AND FUTURE GROWTH - Handy Bugiman; Tota Pirdo Kasih; Zheng Kai (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
This paper provides a comprehensive review of Indonesia's logistics sector, analyzing its performance, structural challenges, and strategic outlook through 2030. As the world's largest archipelago with a robust GDP growth of 5% in 2024, Indonesia possesses a resilient domestic market yet faces significant hurdles in logistics efficiency. The study highlights that Indonesia ranks 61st in the World Bank's Logistics Performance Index (LPI), lagging behind ASEAN peers due to critical bottlenecks in customs clearance and physical infrastructure. To address these issues, the sector is currently being reshaped by a "triad" of strategic policies: investment liberalization through the Omnibus Law, digitalization via the National Logistics Ecosystem (NLE), and improved maritime connectivity through the Sea Toll program, which has successfully reduced regional price disparities from 14.2% to 10.25%. Furthermore, the paper projects a transformative shift toward a green and decentralized supply chain, driven by the implementation of the B50 biodiesel roadmap, a 49% growth in the domestic electric vehicle market, and the relocation of the capital to Nusantara (IKN). The findings conclude that while high logistics costs persist, the convergence of infrastructure continuity and digital reform is positioning Indonesia to evolve from a fragmented market into a pivotal maritime logistics hub.